Prevalence of sexually transmitted infections and immunization status among registered sex workers: A pilot study in lower Bavaria, Germany - Fabian Standl; Lena Senger; Heribert Stich (PLoS ONE, 2025)
Background Sex workers are often considered at elevated risk for sexually transmitted infections (STIs). This pilot study describes the socio‑epidemiological characteristics of registered sex workers in a rural German setting, estimates the prevalence of four STIs (HIV, hepatitis B [HBV], hepatitis C [HCV], and syphilis [lues]), compares these with the local population, and assesses HBV immunization coverage. Methods Under §10 of the Prostitute Protection Act (ProstSchG), annual health consultations are mandatory; voluntary serologic testing is permitted under §19 of the Infection Protection Act. We conducted a retrospective observational monocentric pilot study using routine consultation records and voluntary serologic results from the Public Health Service (PHS) of Landshut (2017–2021). In total, 523 consultations were documented; 99 blood samples from 48 registered sex workers (2019–2021) were analyzed. Primary screening assays were followed by confirmatory tests when indicated. Crude point/period prevalences and 95% confidence intervals (95% CI) were calculated. HBV immunization was defined according to Standing Committee on Vaccination (STIKO) recommendations. Results The cohort was predominantly female (n = 47; 97.9%), mean age 34.8 ± 11.2 years; 85.3% (n = 41) had a migration background (n = 27; 56.3% from Eastern EU countries). No acute HIV, HBV, or HCV infection was detected. Evidence of past HBV infection (anti‑HBc) was found in n = 7 (14.6%; 95% CI: 6.8–26.5), past HCV in n = 1 (2.1%; 95% CI: 0.2–9.3). Syphilis serology was reactive in 12.5% (n = 6), with n = 2 (4.2%; 95% CI: 0.9–12.7) meeting criteria for treatment‑requiring infection. HBV vaccine‑induced immunity was documented in 43.8%; only 29.2% achieved titers ≥100 mIU/ml. Compared with regional surveillance data, the prevalence of acute notifiable STIs among sex workers was not increased. Conclusions In this rural setting, acute notifiable STIs were uncommon among registered sex workers, while past HBV infection and suboptimal HBV immunization were frequent. Public health efforts should prioritize HBV vaccination and syphilis prevention or treatment, and expand low‑threshold, trusted services tailored to this workforce.